Costurile sociale și calitatea vieții - Manea, Livius (Calitatea Vieții, 1993)
This paper points out a certain polysemic degree of the notion: "social costs", taking into account its different acceptions granted especially in comparison with social change. Having the significance of an evaluation, of an comparison between the consumed means and the obtained effects, the characteristics of the "social costs" depends upon the position of the assessor. Between the quality of life and the social costs there comes a negative correlation: a high level of quality of life corresponds to reduced social costs and reversely.